PEMANFAATAN TEPUNG AMPAS KELAPA DALAM PEMBUATAN KERUPUK SAGU - THERESIA YOSEFA; FARIDA HANUM HAMZAH; RAHMAYUNI RAHMAYUNI (Universitas Riau, 2018)
Crackers is crispy snack food which is favored by the folk to consume. The purpose of this research was to getthe best formulation of sago starch and coconut pulp flour on the quality of sago crackers which meet SNI 01-2713-1999. This research used a Completely Randomized Design (CRD) with five treatments and threereplications. Data were statistically analyzed by Analysis of Variance (ANOVA) and followed by Duncan’sNew Multiple Range Test (DNMRT) at level 5%. The treatments of this research were TSA1 (sago starch 95 :coconut pulp flour 5), TSA2 (sago starch 90 : coconut pulp flour 10), TSA3 (sago starch 85 : coconut pulpflour 15), TSA4 (sago starch 80 : coconut pulp flour 20), and TSA5 (sago starch 75 : coconut pulp flour 25).The parameters observed were moisture, ash, protein, crude fiber, swelling power, colour, taste, aroma,crispiness, and overall acceptance hedonic. The best treatment of crackers was TSA3 which had moisturecontent 2.41%, ash content 2.10%, protein content 2.51%, crude fiber content 10.81%, swelling power35.89%, whitish brown (2.90), slightly scented coconut (2.87), somewhat coconut taste (2.93), texturecrispiness (2.10), and overall acceptance hedonic test of crackers was preferred by the panelist.